Description of Family Knowledge on Children's First Aid With Dehydration in RT 003 Village Bani City - Esther Vebiyola Sihombing (Jurnal sosial dan sains, 2022)
Background: Diarrhea is still the main cause of death in the world, accounting for 5-10 million deaths per year. The magnitude of the problem can be seen from the high morbidity and mortality due to diarrhea. The World Health Organization (WHO) estimates that 4 billion cases occur in the world and 2.2 million of them die and most of them are children under the age of 5 years. According to data in America, each child experiences 7-15 episodes of diarrhea with an average age of 5 years. Purpose: This study aims to develop processed nutmeg products, namely Sukade and nutmeg juice and to determine the acceptance of these products based on organoleptic tests. Method : This type of research is descriptive research. used a descriptive approach to obtain a description of the family's knowledge of providing first aid to children with diarrhea with dehydration. Results: The results showed that the profession of parents affects the knowledge of first aid for children with diarrhea and dehydration. Conclusion: It is concluded that parents with entrepreneurial professions and/or family members who as students have more knowledge about first aid for children with diarrhea with dehydration compared to parents with professions as farmers, casual laborers and domestic work.